Two new Species of Marasmius (Basidiomycetes, Marasmiaceae) from a Xeric Zone of Argentina - Papinutti, Víctor Leandro (2011)
M. rosatus and M. pseudoquercophilus are proposed as new species. Detailed descriptions and illustrations of their macro- and microscopic characters are provided. The adaptation of M. rosatus and M. pseudoquercophilus to their xeric habitat is a fascinating aspect of both new species.